Cold zero : a thriller - Thor, Brad; Larsen, Ward (Atria Books, 2026)
"Hemisphere Airlines Flight 777--the most advanced jetliner ever built--disappears without a trace over the North Pole. Crippled by sabotage, it crash-lands on the ice, stranding the surviving passengers in a wasteland of frigid cold and chaos. The real storm, however,is still coming. Hidden inside the wreckage is the prototype for a revolutionary piece of technology that could upend the balance of world power. Now Washington, Moscow, and Beijing are racing to be the first on scene to retrieve it--at any cost. Trapped in the middle ofthe world's most dangerous flashpoint are CIA operative Kasey Sheridan and former fighter pilot turned first officer, Brett Sharpe. Hunted by enemy forces, they must spirit both the device and its creator across the ice to safety--before rival superpowers turn the Arcticinto a war zone. With the clock ticking and the temperature dropping, the fate of the free world is about to be decided at the top of the globe."--Provided by publisher.